GEOCHEMISTRY OF THE KOMATIITE-THOLEIITE ROCK ASSOCIATION IN THE VEDLOZERO-SEGOZERO ARCHEAN GREENSTONE BELT, CENTRAL KARELIA - Svetov S.A. (My University, 2001)
High-Mg volcanics of the komatiite and tholeiite types are widespread in the greenstone belts of Karelia. Their geochemistry and isotopic features were examined using representative successions of the Late Archean Vedlozero-Segozero greenstone belt in central Karelia. The overall thickness of the rocks of the komatiite-tholeiite associations ranges from 2.8 (at Koikary) to 1.5-1.0 km (at Palasel'ga and Sovdozero). The sequences are made up of massive, pillow, and variolitic differentiated lava flows with thin beds of tuff material. The contents of pyroclastic facies do not exceed 3-5% of the overall rock volumes. Tholeiitic basalts overlay komatiites or alternate with them. The successions are dominated by pyroxenitic and basaltic komatiites and Mg-tholeiites. The Sovdozero structure is volumetrically dominated by peridotitic komatiites. The rocks are altered to the greenschist and epidote amphibolite metamorphic facies. Based on the CaO/Al 2O 3 ≈ 0.8 and Al 2O 3/TiO 2 ≈ 22 ratios and on the HREE patterns (Gd/Yb) n = 0.99-1.17, the komatiites are classed with the Al-undepleted type. Compared with the komatiitic lavas, compositionally analogous tuffs have lower concentrations of Al 2O 3 (<8%), are higher in CaO (7-9%), and lower in alkalis. The tholeiites of the belt are geochemically close to basaltic komatiites. Based on experimental results, we calculated the P-T conditions of komatiitic magma generation. The melts were produced during the process of a partial (45-60%) melting of a mantle source with the origin of Ol + Opx residue at depths of 210-240 km, under pressures of 6-7 GPa, and at temperatures of 1780-1845°C in the source (which is 220-280°C higher than the model temperature values in the mantle at 2.9-3.1 Ga). The maximum temperature of the melt during its eruption was as high as 1560-1615°C. The Sm-Nd age of the komatiite association is 2893 ± 110 Ma (ε Nd =+1.2, MSWD = 7) for the Palasel'ga structure and 2944 ± 170 Ma (ε Nd = +1.7, MSWD = 2) for the Koikary structure. The high-Mg volcanic rocks of the Vedlozero-Segozero greenstone belt were produced at 2921 ± 55 Ma (ε Nd = +1.5, MSWD = 5) which is consistent with U-Pb ages of acid volcanics.
Keywords: Archean; greenstone belts; Karelia; Precambrian::Archean; Докембрий::Архей